mPer1 promotes morphine-induced locomotor sensitization and conditioned place preference via histone deacetylase activity - Perreau-Lenz, Stéphanie; Spanagel, Rainer (Psychopharmacology, 2017)
Rationale: Previous studies have shown that repeated exposure to drugs of abuse is associated with changes in clock genes expression and that mice strains with various mutations in clock genes show alterations in drug-induced behaviors. Objective: The objective of this study is to characterize the role of the clock gene mPer1 in the development of morphine-induced behaviors and a possible link to histone deacetylase (HDAC) activity. Methods: In Per1 Brdm1 null mutant mice and wild-type (WT) littermates, we examined whether there were any differences in the development of morphine antinociception, tolerance to antinociception, withdrawal, sensitization to locomotion, and conditioned place preference (CPP). Results: Per1 Brdm1 mutant mice did not show any difference in morphine antinociception, tolerance development, nor in physical withdrawal signs precipitated by naloxone administration compared to WT. However, morphine-induced locomotor sensitization and CPP were significantly impaired in Per1 Brdm1 mutant mice. Because a very similar dissociation between tolerance and dependence vs. sensitization and CPP was recently observed after the co-administration of morphine and the HDAC inhibitor sodium butyrate (NaBut), we studied a possible link between mPer1 and HDAC activity. As opposed to WT controls, Per1 Brdm1 mutant mice showed significantly enhanced striatal global HDAC activity within the striatum when exposed to a locomotor-sensitizing morphine administration regimen. Furthermore, the administration of the HDAC inhibitor NaBut restored the ability of morphine to promote locomotor sensitization and reward in Per1 Brdm1 mutant mice. Conclusions: Our results reveal that although the mPer1 gene does not alter morphine-induced antinociception nor withdrawal, it plays a prominent role in the development of morphine-induced behavioral sensitization and reward via inhibitory modulation of striatal HDAC activity. These data suggest that PER1 inhibits deacetylation to promote drug-induced neuroplastic changes.